Analisis Tingkat Serapan Dan Daya Tampung Karbon Tanaman Mangrove di Desa Munte - Syamsir W Syamsir W; Nurmalasari Nurmalasari; Sunarti Cambaba (Jurnal Biologi Babasal, 2023)
Abstract: One of the benefits of mangrove plants is to reduce pollution and reduce air pollution. The purpose of this study was to find out how much carbon absorption and storage capacity was carried out by mangrove plants in Munte Village. This type of research is a qualitative descriptive analysis. This research will be carried out in August 2021 on the coast of Munte Village. The data obtained were analyzed using density calculation analysis (Density), Calculation of Aboveground Biomass Value (Stems), Calculation of Belowground Biomass Value (Roots), Calculation of Total Biomass Value, Calculation of Carbon Content, and Calculation of carbon dioxide absorption. on transect 1 the biomass was 11280.58% for the species Sonneratia alba and the smallest was 3.82cm with a biomass of 7.27% for the species Avicennia officinalis. So that a total carbon biomass of 14572.23% was obtained, and a total carbon content of 7286.12% and a carbon absorption of 26740.04% were obtained. In transect 2, the biomass was 6309.51% for Avicennia officinalis and the smallest was 3.18 cm with a biomass of 4.77% for Avicennia officinalis. In order to obtain a total carbon biomass of 9106.35% and a total carbon content of 4553.17% and a carbon absorption of 16710.15%. Keywords: Carbon biomass, Mangrove, Munte Village